A Bidirectional Bending Fibre-Reinforced Soft Actuator Robotic Glove for Finger Rehabilitation - Wen Pin, Gooi; Feng, Hor Xian; Ling, Leow Pei (International Journal of Integrated Engineering, 2022)
Finger rehabilitation robots are developed to assist therapists in performing rehabilitation processes on patients. The repetitive flexion and extension have shown positive outcome in improving functionality of fingers among post-stroke patients. However, these robots are made of rigid structures and actuators such as pulleys and motors which pose danger to the delicate human fingers. This paper proposes a bidirectional bending fibre-reinforced soft actuator as an alternative actuator for fingers rehabilitation robots. The developed bidirectional bending soft actuator successfully achieved bending angle of 269.5Ëš at 70 kPa input air pressure. Shrinking electrical tubes were attached to the bidirectional bending soft actuator to produce bending motion which mimic the motion of finger. The modified bidirectional bending soft actuator was used to construct finger rehabilitation glove and achieved bending angle of 98.5Ëš at 90 kPa for flexion motion.